MASK 2017: ARIA digitally‐enabled, integrated, person‐centred care for rhinitis and asthma multimorbidity using real‐world‐evidence. Issue 1 (25th October 2018) - Bousquet, J.; Arnavielhe, S.; Bedbrook, A.; Bewick, M.; Laune, D.; Mathieu‐Dupas, E.; Murray, R.; Onorato, G. L.; Pépin, J. L.; Picard, R.; Portejoie, F.; Costa, E.; et al.
Abstract: mHealth, such as apps running on consumer smart devices is becoming increasingly popular and has the potential to profoundly affect healthcare and health outcomes. However, it may be disruptive and results achieved are not always reaching the goals. Allergic Rhinitis and its Impact on Asthma (ARIA) has evolved from a guideline using the best evidence‐based approach to care pathways suited to real‐life using mobile technology in allergic rhinitis (AR) and asthma multimorbidity. Patients largely use over‐the‐counter medications dispensed in pharmacies. Shared decision making centered around the patient and based on self‐management should be the norm. Mobile Airways Sentinel networK (MASK), the Phase 3 ARIA initiative, is based on the freely available MASK app ( the Allergy Diary, Android and iOS platforms). MASK is available in 16 languages and deployed in 23 countries. The present paper provides an overview of the methods used in MASK and the key results obtained to date. These include a novel phenotypic characterization of the patients, confirmation of the impact of allergic rhinitis on work productivity and treatment patterns in real life. Most patients appear to self‐medicate, are often non‐adherent and do not follow guidelines. Moreover, the Allergy Diary is able to distinguish between AR medications. The potential usefulness of MASK will be further explored by POLLAR (Impact of Air Pollution on Asthma and Rhinitis), a new Horizon 2020 project using the Allergy Diary .